2018
DOI: 10.1186/s13148-018-0542-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of ID4 in breast cancer: tumor suppressor or oncogene?

Abstract: BackgroundInhibitor of differentiation protein 4 (ID4) is a dominant negative regulator of the basic helix-loop-helix (bHLH) family of transcription factors. During tumorigenesis, ID4 may act as a tumor suppressor or as an oncogene in different tumor types. However, the role of ID4 in breast cancer is not clear where both an oncogenic and a tumor suppressor function have been attributed. Here, we hypothesize that ID4 behaves as both, but its role in breast differs according to the estrogen receptor (ER) status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…The data of this study, showing that Id4 may act to impede the evolution of lung cancer metastasis, are similar to those from prostate cancer [41,42], glioblastoma [44], and thyroid tumors [52]. Recently, Nasif and his colleague demonstrated that Id4 is significantly methylated in ER+ breast tumors [40]. On the other hand, Cheng et al also found that lncRNA SNHG7 could regulate the expression of Id4 via sponging miR-342-3p in pancreatic cancer [53].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The data of this study, showing that Id4 may act to impede the evolution of lung cancer metastasis, are similar to those from prostate cancer [41,42], glioblastoma [44], and thyroid tumors [52]. Recently, Nasif and his colleague demonstrated that Id4 is significantly methylated in ER+ breast tumors [40]. On the other hand, Cheng et al also found that lncRNA SNHG7 could regulate the expression of Id4 via sponging miR-342-3p in pancreatic cancer [53].…”
Section: Discussionsupporting
confidence: 76%
“…Until now, the role of Id4 in cancer has remained ambiguous [39][40][41][42][43][44][45]. Although much evidence has suggested the different roles of Id4 in various cancers, the function of Id4 in lung cancer metastasis requires more careful analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The biological mechanism of Id-4 as a tumor suppressor is not understood fully. Aberrant promoter methylation of Id-4 followed by the decreased expression of Id-4 is one of the potential molecular mechanisms, which has been confirmed in prostate cancer, 23 breast cancer, 15 lung cancer, 24 colorectal cancer, 25 and lymphocytic leukemia. 19 Besides, Pankaj Sharma et found that Id-4 could heterodimerize with Id-1, −2 and −3 with consequent reactivation of DNA transcription, thus antagonizing the biological activities of such Id proteins.…”
Section: Discussionmentioning
confidence: 90%
“…Sirnes et al reported that GJC1 promoter methylation played a crucial role in colorectal cancer [38] and follicular lymphoma [39]. ID4 serves as hypermethylation gene and tumor suppressor gene in breast cancer [40,41] and acute leukemia [42,43]. ID4 promoter methylation was also correlated with the risk of prostate cancer [44,45].…”
Section: Discussionmentioning
confidence: 99%